Arctic Region: historical presence and current socioeconomic and cultural problems - Junquera Rubio, Carlos (Observatorio Medioambiental, 2011)
The Circumpolar region and indigenous peoples of the North have held a very special fascination for peoples in the temperate zones. The far northern peoples of Thule fascinated the scholars of Greece and Rome. The terms which describe the Circumpolar region such as cold, inhospitable, hostile, remote, inaccessible, etcetera. The numerous ethnic minorities living along the Circumpolar margins and they are an excellent example of humans groups whose material and spiritual culture has been forced to give way to the southern majority culture. In 1976, I began a study in four small communities of hunters and fishermen on the Mackenzie River on the NWT (Canada). This investigation was supported by the Federal Government of Canada (Foreign Office, Project Nº D-515-I-1999). The technique I used was that of participant observation. The subject of my research was the processes of change in the settlement of Norman Wells, Fort Norman and Fort Good Hope and others small communities with Inuit, Dènè Indians and Métis population.